Dynamics of agricultural land, the park of tractors and agricultural machinery and the total production obtained South of Romania during 2005 - 2010 - Teodora Ivascu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 3rd Edition of the International Symposium, October 2012, Bucharest, 2012)
The present situation of Romanian agriculture is characterized by many socio-economic problems, low yields and competitive, driven mainly by incomplete use of material resources, financial and human. Farms in Romania are extremely numerous and varied, and their physical size does not allow the application of appropriate technologies. Although some progress has been made to maintain an excessive number of individual farms, small and very small, inefficient, as a small number of large and very large units whose activity was not restructured to become compliant with the requirements of the single market.
Keywords: 330; agricultural holdings; agricultural land; agricultural land use; agricultural production.